Antibiotics in Food Chain: The Consequences for Antibiotic Resistance - Shashi B. Kumar; Shanvanth R. Arnipalli; Ouliana Ziouzenkova (MDPI AG, 2020)
Antibiotics have been used as essential therapeutics for nearly 100 years and, increasingly, as a preventive agent in the agricultural and animal industry. Continuous use and misuse of antibiotics have provoked the development of antibiotic resistant bacteria that progressively increased mortality from multidrug-resistant bacterial infections, thereby posing a tremendous threat to public health. The goal of our review is to advance the understanding of mechanisms of dissemination and the development of antibiotic resistance genes in the context of nutrition and related clinical, agricultural, veterinary, and environmental settings. We conclude with an overview of alternative strategies, including probiotics, essential oils, vaccines, and antibodies, as primary or adjunct preventive antimicrobial measures or therapies against multidrug-resistant bacterial infections. The solution for antibiotic resistance will require comprehensive and incessant efforts of policymakers in agriculture along with the development of alternative therapeutics by experts in diverse fields of microbiology, biochemistry, clinical research, genetic, and computational engineering.